TEAMWORK STRATEGIES IN BUILDING INTERPERSONAL RELATIONSHIPS AT THE MINISTRY OF RELIGION OF WEST ACEH - Dara Vaza Ulvia; Sri Rahmi Sri Rahmi (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2026)
Teamwork is a crucial element in public service organizations as it is not only task-oriented but also plays a strategic role in building healthy interpersonal relationships among employees. The quality of interpersonal relationships, such as trust, empathy, and openness, greatly influences the effectiveness of communication and work coordination. This study aims to analyze the forms and strategies of teamwork implemented at the Ministry of Religious Affairs of West Aceh, examine its impact on the quality of interpersonal relationships among employees, and identify the supporting and inhibiting factors in its implementation. This research employed a descriptive qualitative approach, with data collected through interviews and documentation. Key informants included organizational leaders and structural officials. Data analysis was conducted using content analysis through data reduction, data display, and conclusion drawing stages. The findings indicate that teamwork is manifested through open and active leadership, continuous coordination mechanisms, collective accountability, and a work culture that emphasizes togetherness and mutual respect. The implementation of teamwork has a positive impact on interpersonal relationships by increasing communication intensity, strengthening mutual trust and empathy, and fostering emotional support and solidarity among employees. Supporting factors include effective communication, clear task distribution, and responsive leadership, while inhibiting factors arise from differences in personality, background, perceptions, and work pressure. This study concludes that teamwork plays a significant role in fostering harmonious interpersonal relationships and contributes to improving the quality of public services.